Hyperpolarized 3He pulmonary functional magnetic resonance imaging prior to radiation therapy - Mathew, Lindsay; VanDyk, Jake; Etemad-Rezai, Roya; Rodrigues, George; Parraga, Grace (Medical physics (Lancaster), 2012)
Purpose: Radiation-induced lung injury (RILI) is the primary dose-limiting toxicity for radiation therapy of the lung, and although the effects of radiation dose on RILI development have been well characterized, the influence of chronic obstructive pulmonary disease (COPD) on the development of RILI and other outcomes is not well understood. The purpose of this small pilot study was to evaluate the relationship between hyperpolarized3He magnetic resonance imaging (MRI) measurements of COPD with RILI and 12-month survival in lung cancer patients undergoing radical radiotherapy and to evaluate the feasibility of pulmonary functional MRI as an image guidance/planning tool for radiation therapy. Methods: Fifteen non-small cell and small cell lung cancer patients underwent pulmonary function tests, x-ray computed tomography (CT), and hyperpolarized3He MRI prior to radical radiation therapy (≥60 Gy). Conventional thoracic 1H and hyperpolarized 3He MRI were acquired to generate ventilation defect percent and the apparent diffusion coefficient for the ipsilateral and contralateral lungs independently. CT was acquired postradiation therapy and qualitatively evaluated for radiological evidence of RILI and 12-month survival was reported. Results: Hyperpolarized3He MRI measurements of COPD classified 10/15 subjects with contralateral lung COPD (CLC), and five subjects without COPD [contralateral lung normal (CLN)]. Of the 10 subjects with CLC, only four had a previous clinical diagnosis of COPD. CT images were acquired postradiation therapy for 13 subjects, and for eight (62%) of these there was qualitative evidence of RILI, including 5/9 CLC and 3/4 CLN subjects. The one-year survival was 2/10 for CLC and 3/5 for CLN subjects. Conclusions: In this small pilot study, we report the use of3He MRI to stratify lung cancer patients based on MRI evidence of COPD and showed that comorbid COPD was present in the majority of lung cancer subjects stratified for radiation therapy. Lung cancer patients with imaging evidence of COPD did not have an increased incidence of RILI compared to patients without COPD. However, preliminary data presented here indicated that one-year survival in COPD subjects was lower than expected based on previously published survival rates, which may have implications for radiation therapy in lung cancer patients with comorbid COPD.